Risk Factors Associated with Hyperbilirubinemia in Newborns at Muhammadiyah Hospital Palembang - Wita Solama; Widya Arisandy; Restu Khoiriah; Sari Lisa Nurjanah; Nadila Ayu Safira (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Neonatal jaundice remains a significant global health challenge, contributing to substantial neonatal morbidity and potential long-term neurological complications if not managed effectively. This study investigated the risk factors associated with hyperbilirubinemia at Muhammadiyah Hospital Palembang. Utilizing an analytical survey with a case-control approach, we compared 30 neonates diagnosed with hyperbilirubinemia (cases) against 30 neonates without the condition (controls). Participants were selected through purposive sampling between October and December 2024. Data were analyzed using chi-square tests and multivariate logistic regression to determine the strength of associations. The analysis revealed that gestational age (OR = 4.2; 95% CI: 1.8–9.5; p < 0.001), type of delivery (OR = 3.8; 95% CI: 1.5–8.2; p < 0.001), male gender (OR = 2.5; 95% CI: 1.1–5.4; p = 0.001), and low birth weight (OR = 5.1; 95% CI: 2.1–11.3; p < 0.001) were significant independent risk factors for hyperbilirubinemia. These findings underscore the necessity for midwives to implement comprehensive early screening and specialized management for high-risk neonates to mitigate the incidence of severe jaundice. Preterm birth and low birth weight are the most critical predictors of neonatal hyperbilirubinemia in this clinical setting, necessitating targeted postnatal surveillance. Keywords: Neonatal Jaundice, Risk Factors, Case-Control Study, Midwifery Care, Low Birth Weight.